Clinical significance of NT-proBNP as a predictive biomarker of depressive symptoms in cardiac patients - Syeda Humayra; Noorazrul Yahya; Chai Jia Ning; Chai Jia Ning; Mohd Asyiq Al-Fard bin Mohd Raffali; Imtiyaz Ali Mir; Abdul Latiff Mohamed; Hanani Abdul Manan; Hanani Abdul Manan (Frontiers in Cardiovascular Medicine)
IntroductionDepression is a significant comorbidity linked to poor subjective and objective health outcomes in cardiac patients. The paucity of data necessitates further research to elucidate the pathophysiological connection between depression and cardiac diseases in the presence of N-terminal pro-brain natriuretic peptide (NT-proBNP). Therefore, the current systematic review investigated the clinical significance of NT-proBNP as a predictive biomarker in cardiac patients with depressive symptoms.MethodsTwo researchers independently performed an extensive search of published literature from inception until April 2024 on PubMed, Web of Science, and Cochrane Library in accordance with the PRISMA guidelines. From a total of 452 records, 29 articles were eligible for full-text review, whereof, data from 14 articles were systematically collated. Based on the Newcastle-Ottawa Scale (NOS) criteria, all studies earned 6–9 stars and were of good quality.ResultsAmong a total population of 4,035, male patients were predominantly higher (n = 2,618, 65.0%). Approximately, 31.3% (n = 1,264) cardiac patients were depressed. The mean age ranged between 56 and 76 and 58–73 years for depressed vs. non-depressed individuals respectively. More than half of the patients presented with heart failure (n = 2,234, 55.4%), followed by acute myocardial infarction (n = 1,368, 34.0%), coronary artery disease (n = 674, 16.7%), and acute coronary syndrome (n = 164, 4.1%). Poor ventricular function (26.1 ± 6.8 to 37.65 ± 12.71) and worsened NYHA class II-III functional symptoms (moderate-marked limitations) were more prevalent in depression. In addition, three studies found that age and female gender were significant risk factors in depressed patients. Significant clinical relevance was established between increased NT-proBNP and depressive symptoms in seven studies. NT-proBNP values ranged between 138 and 12,000 pg/ml vs. 108 to 6,000 pg/ml for depressed vs. non-depressed patients.ConclusionThe presence of elevated NT-proBNP in depression demonstrated adverse cardiovascular outcomes and played a crucial role in predicting the clinical prognosis. Future NT-proBNP studies with predefined follow-up period at different time intervals, and in clinically depressed patients are highly recommended.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier (CRD42024536115).